Global reporting of progress towards elimination of hepatitis B and hepatitis C. (April 2023) - Cui, Fuqiang; Blach, Sarah; Manzengo Mingiedi, Casimir; Gonzalez, Monica Alonso; Sabry Alaama, Ahmed; Mozalevskis, Antons; Séguy, Nicole; Rewari, Bharat Bhushan; Chan, Po-Lin; Le, Linh-vi; Doherty, Meg; Luhmann, Niklas; et al.
Summary: Background: The 69th World Health Assembly endorsed the global health sector strategy on viral hepatitis to eliminate viral hepatitis as a public health threat by 2030. Achieving and measuring the 2030 targets requires a substantial increase in the capacity to test and treat viral hepatitis infections and a mechanism to monitor the progress of hepatitis elimination. This study aimed to identify the gaps in data availability or quality and create a new mechanism to monitor the progress of hepatitis elimination. Methods: In 2020, using a questionnaire, we collected empirical, systematic, modelled, or surveyed data—reported by WHO country and WHO regional offices—on indicators of progress towards elimination of viral hepatitis, including burden of infection, incidence, mortality, and the cascade of care, and validated these data. Findings: WHO received officially validated country-provided data from 130 countries or territories, and used partner-provided data for 70 countries or territories. We estimated that in 2019, globally, 295·9 million (3·8%) people were living with chronic hepatitis B virus (HBV) infection and 57·8 million (0·8%) people were living with chronic hepatitis C virus (HCV) infection. Globally, there were more than 3·0 million new infections with HBV and HCV and more than 1·1 million deaths due to the viruses in 2019. In 2019, 30·4 million (95% CI 24·3–38·0) individuals living with hepatitis B knew their infection status and 6·6 million (5·3–8·3) people diagnosed with hepatitis B received treatment. Among people with HCV infection, 15·2 million (95% CI 12·1–19·0) had been diagnosed between 2015 and 2019, and 9·4 million (7·5–11·7) people diagnosed with hepatitis C infection were treated with direct-acting antiviral drugs between 2015 and 2019. Interpretation: There has been notable global progress towards hepatitis elimination. In 2019, 30·4 million (10·3%) people living with hepatitis B knew their infection status, which was slightly higher than in 2015 (22·0 million; 9·0%), and 6·6 million (22·7%) of those diagnosed with hepatitis B received treatment, compared with 1·7 million (8·0%) in 2015. Mortality from hepatitis C has declined since 2019, driven by an increase in HCV treatment ten times that of the strategy baseline. However, an estimated 89·7% of HBV infections and 78·6% of HCV infections remain undiagnosed. A new global strategy for 2022–30, based on these new estimates, should be implemented urgently to scale up the screening and treatment of viral hepatitis. Funding: World Health Organization.